(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
This research project refers to a Filipino delicacy called leche flan. Filipinos love to eat sweet foods as snacks or dessert that is why the researchers chose to innovate the traditional leche flan by adding malunggay as its new flavor. The researchers chose Malunggay because they wanted to promote the nutritious value of this vegetable as a dessert, the product is called “Malunggay Leche Flan” because we made an innovative version using Malunggay leaves as the main ingredient. We chose Malunggay to complement with our Leche flan because we wanted to introduce a nutritious dessert that will break our customer’s sweet cravings by our newest product and be sold at Base Memo Dessert Shop, where our costumer can buy our healthy, nutritious and delicious products with a high-quality service with an affordable price. The Researchers used survey method to gather information from the respondents about the research product because it is more efficient and time conserving on data gathering by using some survey questionnaire that is distributed and answered by the respondents who tasted the product. They do the survey to 100% of the respondents or equal to 10 respondents to show the nutritive value of the product. The survey questionnaire is created by the information about the research project. The Researchers found out that 9 out of 10 respondents liked the Malunggay twist on Leche Flan. As a result, 9 of10 agreed that they like the twist of malunggay in a leche flan. Filipinos love to eat sweet foods as snack or dessert and one of their most favorite desserts is leche flan. It is a sweet and creamy custard with caramelized sugar. It is the traditional delicacy of the country. From the old version of leche flan, researchers innovated the typical flavor to a new one. We conducted a survey to gather information from the randomly selected respondents to taste and give feedbacks regarding our product. 9 out of10 respondents liked the innovated flavor. This made the researchers more focused in conducting this research for them to gather the results they needed for this research. The researchers chose this product because it promotes a healthier and nutiritious twist that is not very well known. Likewise, according to the Feasibility Study on the Establishment of Graham Flan Dessert at SM Fairview that leche flan is one of the most popular dessert in our country and has to be innovated in such nutritious ways.